The role of charged residues mediating low affinity protein–protein recognition at the cell surface by CD2 - Davis, Simon J. (The National Academy of Sciences, 1998)
Insights into the structural basis of protein–protein recognition have come principally from the analysis of proteins such as antibodies, hormone receptors, and proteases that bind their ligands with relatively high affinity (K(a) ≈ 10(9) M(−1)). In contrast, few studies have been done on the very low affinity interactions mediating cell adhesion and cell–cell recognition. As a site of protein–protein recognition, the ligand binding face of the T lymphocyte cell–cell recognition molecule, CD2, which binds its ligands 10(4)- to 10(5)-fold more weakly than do antibodies and proteases, is unusual in being both very flat and highly charged. An analysis of the effect of mutations and ionic strength on CD2 binding to its ligand, CD48, indicates that these charged residues contribute little, if any, binding energy to this interaction. However, the loss of these charged residues is shown to markedly reduce ligand-binding specificity. Thus, the charged residues increase the specificity of CD2 binding without increasing the affinity. This phenomenon is likely to result from a requirement for electrostatic complementarity between charged binding surfaces to compensate for the removal, upon binding, of water interacting with the charged residues. It is proposed that this mode of recognition is highly suited to biological interactions requiring a low affinity because it uncouples increases in specificity from increases in affinity.